2002
DOI: 10.1051/0004-6361:20020161
|View full text |Cite
|
Sign up to set email alerts
|

δScuti stars in Praesepe

Abstract: Abstract. We present the results of a large international spectroscopic campaign on the δ Scuti star BN Cnc. Combining observations from five observatories taken over more than two weeks, we calculate line indices of the Hα line. A line index is the integrated line flux in a software filter divided by the continuum flux. We demonstrate that this can be used in combination with simultaneous photometry to classify the oscillation modes. We recover all the frequencies also found from photometry and assign likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In this way, the line index can be thought of as being similar to the Strömgren Hβ index, calculated using software filters. (For a justification of the term 'line index' as an analogue to a colour index, see Dall et al 2002.) The software for calculating line indices has been collected in a software package called IX, as described by Dall (2000).…”
Section: T H E L I N E I N D E Xmentioning
confidence: 99%
See 3 more Smart Citations
“…In this way, the line index can be thought of as being similar to the Strömgren Hβ index, calculated using software filters. (For a justification of the term 'line index' as an analogue to a colour index, see Dall et al 2002.) The software for calculating line indices has been collected in a software package called IX, as described by Dall (2000).…”
Section: T H E L I N E I N D E Xmentioning
confidence: 99%
“…We measure the line index, a quantity that depends on the temperature and surface gravity sensitivity of the equivalent width. It is defined as (Dall et al 2002), where C x is the continuum count level at pixel x , S x is the source count level and W L italicx is a Gaussian‐like weighting function for the line in question. The value of C x is found using C x =∑ S x W C italicx/∑ W C italicx, where W C italicx is a broad filter function and is also Gaussian‐like.…”
Section: The Line Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…Several variability surveys in the Praesepe cluster have been undertaken (e.g., Breger 1970;Frandsen et al 2001, Dall et al 2002 and have revealed a number of low-amplitude δ Sct stars. The pulsations of these stars are of interest, because as cluster members they share similar properties such as chemical abundance and their distances are accurately known.…”
Section: Introductionmentioning
confidence: 99%